Analysis of Employee Welfare Issues at CV. Anugrah Bersama Cahaya Bookstore using the Perspective of Maqosid Syariah - Harahap, Satria Mariqom; Imsar , Imsar; Jannah, Nurul (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to determine the welfare of employees at CV bookstores. Anugrah Bersama Cahaya uses a Maqasid sharia perspective regarding Hifdz al-mal at the dharuriyat level which is researched from the problems that exist in bookstores by looking at the state of mind of employees in dealing with existing problems. and how employees deal with this influence on welfare. Methodology: The research method uses Qualitative research was conducted using a descriptive approach. This research used interviews for data collection, and the interview process was carried out with four bookstore employees. Results: There are several problems in bookstores, including delays in salary payments, which can occur when the company experiences a decline in sales. The company's purchases/spending is greater than its income, so the company experiences a decline in sales. Salary does not match the job; in the bookstore, the job does not match the salary because the company is in a developing stage. Excessive working hours can occur because the company is still in the developing stage. Limitations: Employee welfare is important for companies because it can prevent employees from moving to other companies and increase motivation and work morale. Contribution: Employee problems in bookstores, such as communicating with management regarding problems in the store, can still be resolved effectively.